Gambaran Upaya Pencegahan Anemia pada Ibu Hamil - Suratiah Suratiah; Putu Erryca; Dewa Ayu Ketut Surinati (Jurnal Gema Keperawatan, 2022)
Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. Efforts to prevent anemia in pregnant women launched by the government are adherence to taking blood-added tablets, conducting Hb checks, conducting antenatal care checks and increasing knowledge of pregnant women about anemia. The purpose of this study was to determine the description of anemia prevention efforts in pregnant women in the Work Area of Sukawati Community Health Center I in 2022. This research was quantitative research with descriptive research design and cross sectional approach. The number of samples as many as 41 pregnant women were selected using a non-probability sampling technique with purposive sampling and the data collection instrument used was a questionnaire. The results showed that efforts to prevent anemia in pregnant women by complying with taking iron tablets found that most of them were in the sufficient category as many as 20 people (48.8%), by conducting a Hb examination most of them were in the sufficient category as many as 25 people (61.0%), by conducting antenatal care examination, most of them were in the good category as many as 31 people (75.6%) and by increasing the knowledge of pregnant women about anemia was mostly in the poor category, namely 23 people (56.1%). Therefore, the conclusion to encourage the dissemination of information about anemia and prevention of anemia in pregnancy to pregnant women through classes for pregnant women or counseling during pregnancy check-ups.